Edward Snowden - the man who shook the world - Vdovin, B. V.; Kulyk, Kateryna; Кулик, Катерина Олександрівна; Кулик, Екатерина Александровна (ТДАТУ, 2019)
Journalists continue to publish documents from Snowden that reveal the secret and unaccountable systems of modern global surveillance.
Keywords: NSA's everyday surveillance; copying top-secret NSA; Foreign Intelligence